Pharmacological mechanism of natural products to treat osteoporosis: a focus on the autophagy - Xin, Chenglong; Zhang, Guangheng; Shen, Zheng; Han, Weibiao; Fan, Ruifeng; Ren, Jiakuo; Zhang, Jianyi; Hao, Yanke; Xin, Jian (Frontiers in Pharmacology, 2025)
Osteoporosis (OP) is a serious public health issue, and fragility fractures resulting from OP are a major cause of death in the elderly. Osteoblast (OB)-mediated insufficient bone formation and osteoclast (OCs)mediated abnormalities in bone destruction can result in OP. Autophagy is the process by which cells degrade and recycle their own proteins and organelles. The differentiation and activity of OBs, OCs, and other bone cells depend on autophagy activity. The regulation of autophagy has the potential to influence the metabolic processes of these cells, which may contribute to the treatment of OP. This paper provided a comprehensive review of the experimental and clinical evidence supporting the use of natural products as potential therapeutic agents for OP. We examined the diverse regulatory effects of natural products on bone cells, including bone marrow mesenchymal stem cells, OBs, and OCs. Additionally, we explore the potential of these natural products to mediate autophagy, a process that may offer novel drug options and provide guidance for future clinical trials.